Lodore, Vol. 1 (of 3) - Shelley, Mary Wollstonecraft, 1797-1851 (Salt Lake City, UT : Project Gutenberg, 2021)
"Lodore, Vol. 1 (of 3)" by Mary Wollstonecraft Shelley is a novel published in 1835. When Lord Lodore dies in a duel, he leaves behind his daughter Ethel and estranged wife Cornelia to navigate a web of legal, financial, and familial challenges. Shelley examines power and responsibility through three contrasting women: the over-dependent Ethel, society-obsessed Cornelia, and the independent intellectual Fanny Derham. The novel explores women's education and social roles within a patriarchal culture that pressured them into dependence. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lodore
Release date is 2021-02-14
Laura Natal Rodrigues at Free Literature (Images generously made available by Hathi Trust Digital Library.)
Keywords: Women -- Social conditions -- 19th century -- Fiction